INFLUENCE OF LOW-SODIUM DIET MANAGEMENT ON THIRST RESPONSE IN END STAGE RENAL DISEASE PATIENTS WITH HEMODIALYSIS - Lisbet Gurning; Jenny Marlindawani Purba; Cholina Trisa Siregar (Belitung Raya Foundation, Indonesia, 2018)
Background: Patients with hemodialysis often have difficulty in controlling their fluid intake although the obedience to follow fluid and dietary restriction is the key of hemodialysis success management. Objective: The aim of this study was to examine the effect of low-sodium diet management on thirst response in end stage renal disease patients with hemodialysis. Methods: This was a quasi-experimental study with pre-posttest with control group design. Using consecutive sampling 88 respondents were selected, which 44 assigned in each group. Thirst distress scale and visual analog scale questionnaire were used for data collection. Wilcoxon and Mann Whitney test were used for statistical analysis. Results: Of the total of respondents, thirty-seven respondents experienced a decrease in thirst distress scale with p= 0.000 (p <0.05); and 30 respondents experienced a decrease in visual analog scale with p=0.000 after given low sodium diet management. There was difference of thirst distress scale score (p=0.008) and visual analog scale of thirst score (p=0.048) between intervention and control group. The importance of continuous of diet education with counseling and home visit can increase self-management behaviors. Conclusion. Low sodium diet management could reduce the thirst response in end stage renal disease patients with hemodialysis.